Differences in Aerobic Fitness between Inpatients and Outpatients with Severe Mental Disorders - Holmemo, Helene Daae-Qvale; Fløvig, John Christian; Heggelund, Jørn; Vedul-Kjelsås, Einar (Frontiers in Psychiatry, 2014)
Abstract Background Patients with severe mental disorders have increased mortality, and cardiovascular disease (CVD) accounts for a large part. Physical inactivity and low aerobic fitness have been recognized as significant risk factors for CVD. In this study, we investigated the differences in aerobic fitness and physical activity between in- and outpatients with severe mental disorders. Method and subjects Fifty in- and outpatients from a regional psychiatric department were included. The patients filled in a questionnaire on physical activity and completed a clinical examination. An estimation of aerobic fitness was calculated for each patient, using gender, age, waist circumference, resting heart rate and physical activity level as variables. Results Inpatients had lower estimated aerobic fitness than outpatients (VO₂peak 42 vs 50 mL•kg-1•min-1, p<0.001). Compared to population data matched for age and gender, inpatients had lower aerobic fitness, while outpatients were not different from the population average. Conclusion Inpatients at a psychiatric department had lower estimated aerobic fitness than outpatients, and a lower aerobic fitness compared to the general population. Our findings suggest that inpatients with severe mental disorders should be considered a high risk group for CVD.